Trading Higher Software Piracy for Higher Profits: The Case of Phantom Piracy - Gopal, Ram D.; Gupta, Alok (Management Science, 2010)
Faced with the sustained problem of piracy that costs nearly $40 billion in annual revenue losses, the software industry has adopted a number of technical, legal, and economic strategies to curb piracy and stem the resulting losses. Our work complements and contributes to the existing literature by exploring the possible effect of another economic lever—product bundling—on the relationship governing piracy and seller profits. The traditional economic rationale of demand pooling from bundling that enables sellers to extract higher surplus and its particular attractiveness for information goods with negligible marginal and bundling costs carry over to our analysis. However, the presence of piracy injects several new facets to our analysis. Bundling creates a shared level of piracy of disparate products, and under certain conditions to the detriment of one of the products. We argue that by construction of the copyright laws, the act of bundling itself can have a deterrence effect. This deterrence effect, along with shared piracy of products and demand pooling are ingredients that together dictate the overall piracy, pricing, profit, and welfare outcomes. Our analysis reveals several interesting insights. Bundling can be profitable even when the very act of bundling increases the piracy level of one of the products in the bundle. Termed phantom piracy, this represents a situation where sellers trade off higher piracy for one product in favor of lower piracy for the other product while deriving overall higher profits. Extensive simulation analysis shows that the region of phantom piracy is vastly expanded when additional products are introduced to the bundle. Conversely, under certain conditions, a profit maximizing seller opts not to bundle even when bundling can serve to lower the overall level of piracy. Price discounts that are typically offered by bundling are sharply deepened when piracy enters the equation. When piracy is a phenomenon to contend with, product bundling always increases consumer surplus even in scenarios where the seller may not realize higher profits. Unlike other forms of price discrimination that are often viewed by consumers with a jaundiced eye as they attempt to extract additional surplus from the consumers, product bundling in the software context can be a win-win scenario for both the buyers and the sellers.